Lipid Profiles, Telomere Length, and the Risk of Malignant Tumors: A Mendelian Randomization and Mediation Analysis - Shupeng Liu; Zhengzheng Fu; Hui Liu; Yinghui Wang; Meijuan Zhou; Zhenhua Ding; Zhijun Feng (Biomedicines)
Background/Objectives: The relationship between lipid profiles, telomere length (TL), and cancer risk remains unclear. Methods: This study employed two-sample Mendelian randomization (MR) with mediation analysis to investigate their causal relationships, examining lipid profiles as exposure, TL as mediator, and nine cancer types as outcomes. We conducted our analysis using two-stage least squares (2SLS) regression integrated with inverse variance weighted (IVW) methods to address potential endogeneity and strengthen our causal inference. Results: we found that unfavorable lipid profiles were causally linked to increased TL (p < 0.05). TL showed positive causal associations with lung and hematologic cancers (OR > 1, p < 0.05). Direct associations were observed between total and low-density lipoprotein (LDL) cholesterol and gastric cancer (OR < 1, p < 0.05), and between remnant cholesterol and colorectal cancer (OR > 1, p < 0.05). Mediation analysis revealed TL as a significant mediator in the pathway from lipid profiles to cancer development (p < 0.05). No horizontal pleiotropy was detected. Conclusions: Our findings suggest that lipid metabolism disorders may influence cancer development through telomere regulation, particularly in lung and hematologic cancers. This emphasizes the importance of lipid management in cancer prevention and treatment, especially for these cancer types.